Association between edoxaban dose, concentration, anti-Factor Xa activity, and outcomes: an analysis of data from the randomised, double-blind ENGAGE AF-TIMI 48 trial. Issue 9984 (6th June 2015) - Ruff, Christian T; Giugliano, Robert P; Braunwald, Eugene; Morrow, David A; Murphy, Sabina A; Kuder, Julia F; Deenadayalu, Naveen; Jarolim, Petr; Betcher, Joshua; Shi, Minggao; Brown, Karen; Patel, Indravadan; et al.
Summary: Background: New oral anticoagulants for stroke prevention in atrial fibrillation were developed to be given in fixed doses without the need for the routine monitoring that has hindered usage and acceptance of vitamin K antagonists. A concern has emerged, however, that measurement of drug concentration or anticoagulant activity might be needed to prevent excess drug concentrations, which significantly increase bleeding risk. In the ENGAGE AF-TIMI 48 trial, higher-dose and lower-dose edoxaban were compared with warfarin in patients with atrial fibrillation. Each regimen incorporated a 50% dose reduction in patients with clinical features known to increase edoxaban drug exposure. We aim to assess whether adjustment of edoxaban dose in this trial prevented excess drug concentration and the risk of bleeding events. Methods: We analysed data from the randomised, double-blind ENGAGE AF-TIMI 48 trial. We correlated edoxaban dose, plasma concentration, and anti-Factor Xa (FXa) activity and compared efficacy and safety outcomes with warfarin stratified by dose reduction status. Patients with atrial fibrillation and at moderate to high risk of stroke were randomly assigned in a 1:1:1 ratio to receive warfarin, dose adjusted to an international normalised ratio of 2·0–3·0, higher-dose edoxaban (60 mg once daily), or lower-dose edoxaban (30 mg once daily). Randomisation was done with use of a central, 24 h, interactive, computerised response system. International normalised ratio was measured using an encrypted point-of-care device. To maintain masking, sham international normalised ratio values were generated for patients assigned to edoxaban. Edoxaban (or placebo-edoxaban in warfarin group) doses were halved at randomisation or during the trial if patients had creatinine clearance 30–50 mL/min, bodyweight 60 kg or less, or concomitant medication with potent P-glycoprotein interaction. Efficacy outcomes included the primary endpoint of all-cause stroke or systemic embolism, ischaemic stroke, and all-cause mortality. Safety outcomes included the primary safety endpoint of major bleeding, fatal bleeding, intracranial haemorrhage, and gastrointestinal bleeding. This trial is registered withClinicalTrials.gov, numberNCT00781391 . Findings: Between Nov 19, 2008 and Nov 22, 2010, 21 105 patients were recruited. Patients who met clinical criteria for dose reduction at randomisation (n=5356) had higher rates of stroke, bleeding, and death compared with those who did not have a dose reduction (n=15 749). Edoxaban dose ranged from 15 mg to 60 mg, resulting in a two-fold to three fold gradient of mean trough drug exposure (16·0–48·5 ng/mL in 6780 patients with data available) and mean trough anti-FXa activity (0·35–0·85 IU/mL in 2865 patients). Dose reduction decreased mean exposure by 29% (from 48·5 ng/mL [SD 45·8] to 34·6 ng/mL [30·9]) and 35% (from 24·5 ng/mL [22·7] to 16·0 ng/mL [14·5]) and mean anti-FXa activity by 25% (from 0·85 IU/mL [0·76] to 0·64 IU/mL [0·54]) and 20% (from 0·44 IU/mL [0·37] to 0·35 IU/mL [0·28]) in the higher-dose and lower-dose regimens, respectively. Despite the lower anti-FXa activity, dose reduction preserved the efficacy of edoxaban compared with warfarin (stroke or systemic embolic event: higher dose pinteraction =0·85, lower dose pinteraction =0·99) and provided even greater safety (major bleeding: higher dose pinteraction 0·02, lower dose pinteraction =0·002). Interpretation: These findings validate the strategy that tailoring of the dose of edoxaban on the basis of clinical factors alone achieves the dual goal of preventing excess drug concentrations and helps to optimise an individual patient's risk of ischaemic and bleeding events and show that the therapeutic window for edoxaban is narrower for major bleeding than thromboembolism. Funding: Daiichi-Sankyo Pharma Development.